Modeling of the I–V Characteristics for LDD-nMOSFETs in Relation with Defects Induced by Hot-Carrier Injection - R. Marrakh; A. Bouhdada (Active and Passive Electronic Components)
The hot-carrier injection is observed increasingly to degrade the I–V characteristics with the scaling of MOS transistors. For the lightly doped drain MOS transistor the injection of the hot-carriers, caused by the high electric field in the MOS structure, is localized in the LDD region. The modeling of the drain current in relation to defects due to the hot-carrier injection allows us to investigate the I–V characteristics and the transconductance of devices. Consequently, we can know the amount of the device degradation caused by these defects in order to find technological solutions to optimize reliability.